Helicobacter and the Potential Role in Neurological Disorders: There Is More Than Helicobacter pylori - Gorlé, Nina; Bauwens, Eva; Haesebrouck, Freddy; Smet, Annemieke; Vandenbroucke, Roosmarijn E. (Frontiers in Immunology, 2021)
Trillions of symbiotic microbial cells colonize our body, of which the larger part is present in the human gut. These microbes play an essential role in our health and a shift in the microbiome is linked to several diseases. Recent studies also suggest a link between changes in gut microbiota and neurological disorders. Gut microbiota can communicate with the brain via several routes, together called the microbiome-gut-brain axis: the neuronal route, the endocrine route, the metabolic route and the immunological route. Helicobacter is a genus of Gram-negative bacteria colonizing the stomach, intestine and liver. Several papers show the role of H. pylori in the development and progression of neurological disorders, while hardly anything is known about other Helicobacter species and the brain. We recently reported a high prevalence of H. suis in patients with Parkinson’s disease and showed an effect of a gastric H. suis infection on the mouse brain homeostasis. Here, we discuss the potential role of H. suis in neurological disorders and how it may affect the brain via the microbiome-gut-brain axis.